2020
DOI: 10.1021/jacs.0c03197
|View full text |Cite
|
Sign up to set email alerts
|

Visible-Light-Induced Radical Carbo-Cyclization/gem-Diborylation through Triplet Energy Transfer between a Gold Catalyst and Aryl Iodides

Abstract: Geminal diboronates have attracted significant attention because of their unique structures and reactivity. However, benzofuran-, indole-, and benzothiophene-based benzylic gem-diboronates, building blocks for biologically relevant compounds, are unknown. A promising protocol using visible light and aryl iodides for constructing valuable building blocks, including benzofuran-, indole-, and benzothiophene-based benzylic gemdiboronates, via radical carbo-cyclization/gem-diborylation of alkynes with a high functi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
35
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 63 publications
(40 citation statements)
references
References 66 publications
2
35
0
1
Order By: Relevance
“…Fluorescence quenching studies and a Stern–Volmer plot revealed that 2a interacts with the excited organo-photocatalyst (Figures S13–S15). This points to involvement of an energy transfer (EnT) mechanism. Visible-light-mediated energy transfer catalysis has remained a relatively underdeveloped field . Interestingly, reported photocatalytic reactions with an acridinium photocatalyst involving alkenes have only been reported to occur via the formation of the corresponding radical cations, subsequently trapped with suitable nucleophiles …”
Section: Resultssupporting
confidence: 60%
“…Fluorescence quenching studies and a Stern–Volmer plot revealed that 2a interacts with the excited organo-photocatalyst (Figures S13–S15). This points to involvement of an energy transfer (EnT) mechanism. Visible-light-mediated energy transfer catalysis has remained a relatively underdeveloped field . Interestingly, reported photocatalytic reactions with an acridinium photocatalyst involving alkenes have only been reported to occur via the formation of the corresponding radical cations, subsequently trapped with suitable nucleophiles …”
Section: Resultssupporting
confidence: 60%
“…This indicates that photocatalyst is not crucial but can improve reaction efficiency. This phenomenon has also been reported by others 54 58 and we envisioned that the photocatalytic cycle could increase the concentration of benzyl radical (from decarboxylation of the carboxyl radical). The control experiment confirmed that the decarboxylative C-N coupling requires light irradiation since no reaction occurred in the dark otherwise under optimized conditions (entry 11).…”
Section: Resultssupporting
confidence: 86%
“…Thus, it was suggested that the gold(II) species would predominantly undergo a SET with another equivalent of aryldiazonium salt to deliver the desired cationic gold(III) complex ( 222) and an aryl radical. However, every now and then a SET from the gold(II) species ( 224) to [Ru] 3+ had to occur to initiate a new radical chain, also under formation of the desired product (222).…”
Section: Stoichiometric Access To Gold(iii) Complexes With Lightmentioning
confidence: 99%
“…The utility of the dinuclear gold(I) complex in energy transfer reactions was recently reported by Hashmi and co-workers using aryl iodide compounds of type 351 for the synthesis of gem-diboronate building blocks 352 (Scheme 102). 222 The reaction merely proceeded by using 1.0 mol % of [Au 2 (μdppm) 2 ] 2+ and 50 mol % of Na 2 CO 3 under light irradiation (entries 1−4). The counteranion of the dinuclear gold(I) also seemed to influence the reaction outcome, while chloride gave 70% of the desired product 352a and triflate yielded 90% (entry 5).…”
Section: Energy Transfer Reactionsmentioning
confidence: 99%